Defining enhanced recovery after resection of peri-hilar cholangiocarcinoma. Issue 8 (August 2019) - Quinn, L.M.; Mann, K.; Jones, R.P.; Bathla, S.; Stremitzer, S.; Dunne, D.F.; Lacasia, C.; Fenwick, S.W.; Malik, H.Z.
Abstract: Introduction: Enhanced recovery after surgery (ERAS) for peri-hilar cholangiocarcinoma (pCCA) has not been described in the literature. This study examined patients undergoing pCCA resection within a standard post hepatectomy ERAS pathway to define achievable targets suitable for these patients. Methods: Patients undergoing pCCA resection at University Hospital Aintree (January 2009–October 2017) were identified. Achievement of key ERAS outcomes was assessed. Patients were stratified on incidence of major complications and pre-operative cardiopulmonary exercise testing. Chi Square and Mann Whitney analyses were undertaken as appropriate. Achievable ERAS targets were derived from patients who did not develop a major complication. Results: 46 patients underwent resection with enhanced recovery. Median age 65 (24 male: 22 female). Key ERAS outcomes in patients who did not experience major complications are described as medians (interquartile range): length of stay 8 days (6−13), duration critical care 2 days (2–4), inotropes 6 h (0−24), epidural 3 days (3–4), early mobilization day 1 (1–2), full mobilization day 3 (3–4), urinary catheter removal day 4 (3–5), NGT removal day 1 (1–2) and restoration oral nutrition day 2 (2–4). Patients deemed high risk pre-operatively or those who developed major complications post-operatively required significantly longer critical care (p = 0.008 and p = 0.002 respectively). Other ERAS targets remained achievable in similar timeframes. Conclusions: ERAS for pCCA is achievable. Applicable ERAS standards are defined which take into account minor complications. High risk patients and those with major complications can be appropriately managed in an ERAS pathway, though there is increased need for critical care support.